The Power of Two : Surviving Serious illness with an Attitude & an Advocate - Monaghan, Brian (Brian Dennis); Monaghan, Gerri (New York, NY : Workman Pub., 2009)
"This much-needed book is for anyone facing cancer, or any other serious medical challenge. And it is a much-needed book for that person's partner or loved one. It is a book that combines an inspiring story of hope, courage, and survival with a compelling practical blueprint for how to be an advocate and make a potentially life-or-death difference in a patient's life. It is a book that has the power to change everything." --Cover, p. 2.
Includes bibliographical references (p. 211-217).
Keywords: Monaghan, Brian -- Health; Monaghan, Brian; Monaghan, Gerri; Melanoma -- Patients -- California -- Biography; Brain -- Tumors -- Patients -- California -- Biography; Lawyers -- California -- Biography; Patient advocacy; Brain Neoplasms -- Personal Narratives; Melanoma -- Personal Narratives; Lawyers -- California -- Biography; Patient Advocacy -- California -- Popular Works; Brain Neoplasms -- therapy -- Popular Works